Characterization of swirl effervescent spray at low Renolds number using response surface methodology / Zulkifli Abdul Ghaffar - Abdul Ghaffar, Zulkifli (2023)
The disintegration of bulk liquid into sprays is known as liquid atomization and could be characterized using a map called the liquid disintegration regime map. Mapping a liquid disintegration regime of any atomizer help in sizing the atomizer for a given desired resulting spray characteristics. However, the map for a type of atomization, namely swirl effervescent atomization, is hardly available. Swirl effervescent atomization has broad advantages within the hybrid category, and it is crucial to map the liquid disintegration regime for this type of liquid atomization. Water acts as the working fluid and air is used as the atomizing gas. Dimensional analysis was applied to determine the dimensionless numbers affecting the spray characteristics (spray angle, breakup length, and droplet diameter). Liquid Reynolds number (ReL), gas Reynolds number (ReG), and swirl chamber length to discharge orifice diameter ratio (ls/do) were the dimensionless numbers acquired.